Menilai Kualitas Laporan Keuangan Pemerintah Daerah dari Aspek Sistem Informasi dan Pengelolaan Aset Daerah - Sukma, Astri Malati; Hidayat, Asep Iwa; Susanty, Aty (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This research aims to determine whether the regional financial management information system and regional fixed asset management have an effect on the quality of regional government financial reports in the West Bandung Regency Regional Government. The independent variable consists of regional financial management information systems and regional fixed asset management, while the dependent variable is the quality of regional government financial reports. This type of research is included in quantitative research, while the research methods used are descriptive and verification methods. The population in this study were employees of the accounting and asset recording section at SKPD in the West Bandung Regency Government. The sampling technique is non-probability sampling using purposive sampling, so the total sample is 94 people. The data analysis used in this research is multiple linear regression analysis using SPSS software. Partial and simulated research results show that leadership and work discipline influence employee performance. This study shows that there is a significant impact from the implementation of the Regional Financial Management Information System and Regional Fixed Asset Management on improving the quality of regional government financial reports.